Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.17957/ijab/15.0246
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of some Extracts from Gamma irradiated Purslane (Portulaca oleracea) Plant

Abstract: To cite this paper: Sallam, E.M. and M.M. Anwar, 2017. Antioxidant activity of some extracts from gamma irradiated purslane (Portulaca oleracea) plant. AbstractPurslane plant is one of the most used medicinal plant listed in the World Health Organization. This paper aims to evaluate the effect of some solvent and different doses of irradiation on antioxidants level and its activity. The extraction of antioxidants was performed by methanol, ethanol and distilled water. Antioxidant activities were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
3
9
1
Order By: Relevance
“…The highest value was for 10 kGy dose. These results are in agreement with those of Ibrahim et al (); Sallam and Mervat () who evaluated the effect of different doses of irradiation on antioxidant level and its activity in pomegranate and purslane plant. Antioxidant activities were determined by Diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging activity, ferric reducing power (FRAP), and β‐carotene bleaching (βCB), they reported that total antioxidant contents and their activities increased with increasing the irradiation dose.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The highest value was for 10 kGy dose. These results are in agreement with those of Ibrahim et al (); Sallam and Mervat () who evaluated the effect of different doses of irradiation on antioxidant level and its activity in pomegranate and purslane plant. Antioxidant activities were determined by Diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging activity, ferric reducing power (FRAP), and β‐carotene bleaching (βCB), they reported that total antioxidant contents and their activities increased with increasing the irradiation dose.…”
Section: Resultssupporting
confidence: 93%
“…It seems that irradiation might induce compose small molecules large of phenolic (Table ), these results agree with Rafiee, Jafari, Alami, and Khomeiri () who mentioned that microwave increased the yield of Phenolic compounds extract from OL compared with maceration method. Ibrahim et al () reported that ethanolic 50% extract of irradiated pomegranate peel and seed at dose level of 6 kGy had higher TPC, TFC, and antioxidant activity compared to 3 and 9 kGy Extraction of irradiated purslane plant at 9 kGy by methanol is considered to be the effective one to obtain natural phenolic acid compounds than at 5 and 7 kGy (Sallam & Mervat, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harrison and Were [ 26 ] studied the irradiation effects of almond skin extracts and found that TPC increased at 4 and 12.7 kGy. A similar increase of TPC and TFC was reported in the literature for irradiated Purslane (Portulaca oleracea) Plant [ 27 ] and Dill herb irradiated at 2, 4, and 8 kGy [ 28 ]. This increase of the TPC is due to the release of phenolic compounds from the glycosidic components and degradation of the larger phenolic molecules into smaller ones by gamma irradiation [ 26 ].…”
Section: Resultssupporting
confidence: 83%
“…The above ground portions of the plant are a part of folk medicine used in several countries due to its high anti-asthmatic, antipyretic, antiascorbic, febrifuge, diuretic, antiseptic, antitussive, vermifuge, and antispasmodic effects (Khazdair et al, 2019;Alu'datt et al, 2019;Catap et al, 2018). Different extracts of the plant have been shown with hypocholesterolemic, bronchodilatory, neuropharmacological, wound healing, analgesic, hypolipidemic, anti-inflammatory, anti-aging, antibacterial, hypoglycemic, antioxidant, and skeletal muscle relaxant (Sallam and Anwar, 2017;Ahmadi et al, 2021;Kaveh et al, 2017). Other studies have reported that Portulaca oleracea L. shows protective effects…”
Section: Introductionmentioning
confidence: 99%